Analisis Kecerdasan Kinestetik, Interpersonal dan Intrapersonal dengan Hasil Belajar Pendidikan Jasmani - Dodi Irwansyah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2018)
The results of learning physical education of students at Kuta Baro MTsN are very lacking, this is of course there is a connection with kinesthetic intelligence, interpersonal and intrapersonal intelligence. The purpose of this study was to see the relationship between kinesthetic intelligence, interpersonal and intrapersonal with the results of physical education learning students of MTsN Kuta Baro Aceh Besar. This type of correlational research using 175 Baro students MTsN students, while the sample technique uses random sampling taken 15% from 25 people, and data analysis using multiple correlation formulas. The results of the study showed that there was a relationship between kinesthetic intelligence, interpersonal intelligence, intrapersonal intelligence with students learning outcomes at Kuta Baro MTsN.